Gambaran Patologi Infeksi Trypanosoma evansi pada Mencit Pascapengobatan dengan Esktrak Ethanol Daun Kipahit (Tithonia diversifolia) (PATHOLOGIC FEATURES OF TRYPANOSOMA EVANSI INFECTION AFTER BEING TREATED WITH ETHANOLIC EXTRACT OF KIPAHIT LEAVES - Wahyuwardani, Sutiastuti; Wardhana, April H; Subekti, Didik T; Siswantoro, Dharwin (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
Trypanosoma evansi is a causative agent of Surra disease, which can cause death on infected animals. Surra disease treatment using commercial drugs are expensive, so that it is necessary to look for an alternative drug based on herbal medicine. The present study was carried out to investigate the pathological feature of infected mice after being treated with ethanolic extract of kipahit leaves ( Tithonia diversifolia ). Forty two male mice weighted 25-30 g of DDY strain were used and divided into seven groups Each group consisted of six mice as replication i.e. uninfected mice as a negative control (P 0), mice infected 104/0.3 mL T. evansi intra peritoneally as a positive control (P 1), uninfected mice treated orally by ethanol extract of kipahit 25 mg/kg BW(P2), infected mice treated orally by ethanol extract of kipahit 25 mg/kg BW then gave booster (P2) on day 6 post infection – double doses (P3), infected mice treated orally by ethanol extract of kipahit 25 mg/kg BW – single dose (P4), infected mice treated by commercial drug – single dose (P5) and infected mice treated by commercial drug – double doses (P6). Anatomy pathological lessions such as splenomegaly, hepatomegaly and pailness of kidney could be identified in mice organs. The histopathologycal lessions such as edema, hemorhhage, infiltration of inflamatory cells and trypanosome parasites in blood vessels could found in liver, kidney, lung, cardiac, spleen tissues of mice, edema also vasculitis found in cerebrum. It was concluded that intraperitoneal administration kipahit ethanol extract at dose 25 mg/BW might potentially reduce the number of T. evansi in the bloodstream of infected animals, but could not prevent and recover from T. evansi inducing organs damage.